From the Laboratory to the Market: A Review of the Research Commercialisation Ecosystem in Nigeria - Oluremi Nurudeen Olaleye; Abdulrahman Babajide Ogunji; Ahmed Adebowale Adedeji; Mutiat Adetayo Omotayo; Johnson Oshiobugie Momoh (Journal of Novel Engineering Science and Technology, 2026)
Nigeria’s 200-plus universities generate substantial research across agriculture, healthcare, and engineering, yet output rarely translates into commercial products. This policy and literature review synthesises evidence from 47 government documents, peer-reviewed articles, and international reports to diagnose the research commercialisation landscape through National Innovation Systems and Triple Helix lenses. Thematic analysis reveals chronic underfunding (0.22% of GDP on R&D), weak university–industry linkages, absence of professional Technology Transfer Offices, and regulatory ambiguity as systemic barriers. Comparative analysis of South Korea, Finland, Malaysia, Rwanda, and Kenya identifies transferable institutional mechanisms. The review proposes a hybrid model combining strategic state direction in priority sectors with bottom-up entrepreneurial support, offering Nigeria-specific implementation pathways including phased R&D investment, sector-focused intermediary agencies, and diaspora engagement mechanisms. Limitations and critiques of commercialisation-first approaches are discussed. Strategic recommendations target policymakers, university administrators, and development partners.